Multiple-focus ultrasound phased-array pattern synthesis: optimal driving-signal distributions for hyperthermia - Ebbini, E.S.; Cain, C.A. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 1989)
A method for computing array element amplitude and phase distributions for direct synthesis of multiple-focus field patterns using ultrasonic phased arrays is shown to be capable of producing desired field levels at a set of control points in the treatment volume. The complex pressure at any of these control points can be chosen to produce the desired power deposition at the point, including reducing the field level to avoid potential hot spots, thus providing a powerful tool for hyperthermia treatment planning. The method also allows the complex excitation vector to be weighted to reduce the dynamic range of the driving signals without disturbing the relative field levels at the control points, allowing near maximum power transfer from the array into the treatment volume.< >